Exosomes in the Diseased Brain: First Insights from In vivo Studies - Levy, Efrat (Frontiers in Neuroscience, 2017)
Extracellular vesicles (EVs) are nanoscale size vesicles secreted by cells and are important mediators of intercellular communication and genetic exchange. Exosomes, EVs generated in endosomal multivesicular bodies, have been the focus of numerous publications as they have emerged as clinically valuable markers of disease states. Exosomes have been mostly studied from conditioned culture media and body fluids, with the difficulty of isolating exosomes from tissues having delayed their study in vivo. The implementation of a method designed to isolate exosomes from tissues, however, has yielded the first insights into characteristics of exosomes in the brain. It has been observed that brain exosomes from murine models of neurodegenerative diseases and human postmortem brains tend to mirror the protein content of the cells of origin, and interestingly, they are enriched with toxic proteins. Whether this enrichment with neurotoxic proteins is beneficial by relieving neurons of accumulated toxic material or detrimental to the brain by propagating pathogenicity throughout the brain remains to be answered. Here is summarized the first group of studies describing exosomes isolated from brain, results that demonstrate that exosomes in vivo reflect complex multicellular pathogenic processes in neurodegenerative disorders and the brain’s response to injury and damage.